O modus operandi do regime fiscal brasileiro no período de 2000 a 2016 - Ulhôa, Wander Marcondes Moreira (2017)
The Brazilian Tax Regime is the result of a liberal political and macroeconomic environment that was consolidated in the late 1990s, whose state action efforts focused on price stabilization, with emphasis on monetary (inflation targets) and fiscal (balanced budget and primary surplus) rules. Here the guidelines of the Macroeconomic Regime are established, ensuring a guide to the actions of the state, regardless the ideological matrix of public managers. In this context, the construction of the Brazilian Tax Regime should be understood, especially with the sanction of Fiscal Responsibility Law (FRL), which set budgetary and fiscal rules for federative entities, in order to ensure inter alia the balance of public accounts and to prevent the state s wasteful action, an essential matter to monetary stability. It was essentially intended that the legal system would restrict state actions in the various public spheres. Hence, it cannot be inferred that FRL obstructed all the discretionary actions of public managers, and there was still a gap to promote changes affecting federative relations, fiscal, tributary renunciations or even an increase of primary public expenses it occurs if the fiscal targets are executed (primary surplus). It is presumed that the best way to assess that there is not an absolute linearity of the Brazilian Tax Regime is to scrutinize its dimensions: (I) Budget and Taxation; (II) Fiscal Federalism; (III) State Companies and Banks; and (IV) Tax Targets. It was concluded that, at different times, the discretionary aspect of state action was increased, in order to mobilize fiscal instruments for different objectives, associated to the specificities of power projects, without changing the central foundations of the Tax Regime. The problem occurs when fiscal revenues are insufficient to reconcile the budget-financial execution of primary expenditure with the need to generate primary surpluses. This fact explains the sanction of Constitutional Amendment n. 95 (New Tax Regime), which will reduce the gap of state actions; after all, it is the main instrument of state intervention with which public spending will be bounded in favor of generating fiscal surpluses to stabilize the debt/Gross Domestic Product (GDP) relation.